Soybean Bio-Active Compounds - El-Shemy, Hany A. (IntechOpen, 2013)
Legumes are important for the diet of a significant part of the world's population; they are a good source of protein, carbohydrates, minerals and vitamins. The "importance of soybean" lies in the overall agriculture and trade and in its contribution to food supply. Soybean contains the highest protein content and has no cholesterol in comparison with conventional legume and animal food sources. Furthermore, soybean is a cheap source of food, and at the same time medicinal due to its genistein, photochemical, isoflavones content. Soybean has been found to be extremely helpful in the fight against heart disease, cancer and diabetes, among others. Soybean protein and calories are presently being used to prevent body wasting often associated with HIV. The importance of soybean nutrition intervention is amplified where medications are unavailable. Its economic potential inherent in a wide range of industrial uses can be harnessed to the benefit of smallholder soybean producers.